The European Union’s and United States of America’s Non–Tariff Measures: Impacts on African Exports - Kareem, Olayinka Idowu (International Food Policy Research Institute, 2016)
There are differentials in the conclusion of scholars as to what undermines Africa’s export flows to the European Union (EU) and United State of America (USA). While the impact of tariffs has been reduced due to the unilateral preferential tariffs granted to Africa by these countries, empirical studies have shown that the frequencies of the incidences of non-tariff measures have increased. However, most of these studies examine only price-related trade restrictions without considering the non–tariff (non-price) measures. In addition, these studies’ conclusions are based on data limited to Africa south of the Sahara. This study fills these gaps by evaluating the impact of non-tariff measures in the EU and USA on African exports. The study covers exports from 25 African countries, spread across three sectors, using a gravity model based on data from 1990 to 2011, which were obtained from World Integrated Trade Solution (WITS). To mitigate the potential endogeneity and heteroscedasticity problems, the generalized method of moments was used in the analysis. This study finds that tariffs are not the cause of Africa’s inability to access export markets in the EU and USA, but that the incidence of the use of non-tariff measures, such as technical barriers to trade, sanitary and phytosanitary measures, etc., have inhibited Africa’s export flows to these markets, such that non-tariff barriers have larger magnitudes and significant in both markets.